SELAMATKAN DANAU TOBA KALAU TIDAK SEKARANG KAPAN LAGI? KALAU BUKAN KITA SIAPA LAGI? - Essay dari Dr. Wilmar E. Simandjorang1; Johnson Kennedy2, Posma Sariguna (Universitas Kristen Indonesia, 2023)
This paper discusses the success of Lake Toba, which is considered the king of all lakes due to its geological, environmental, biological, and cultural diversity. This unique value has made Lake Toba a famous tourist destination worldwide. Before the 1960s, the local community managed the lake with traditional wisdom based on the principle of MARSIADAPARI and the prohibition of TOKKA, which aimed to preserve the environment and biodiversity, resulting in a prosperous life and preserved environment. However, after the enactment of PMDN and PMA laws, the exploitation of Lake Toba's natural resources began, leading to deforestation, the burning of land, and using chemical fertilizers, causing damage to the soil's nutrients and runoff into Lake Toba. The lack of protected forest supervision has also severely reduced the lake's water level. Plastic waste has become a significant problem in the area, with plastic waste dumped in farmland and rivers leading to Lake Toba. The study suggests that the government needs to address the issues of environmental destruction and prioritize protecting Lake Toba's natural resources to maintain its unique value and continue attracting tourists. Keywords: Toba Lake, Save, When Next, Who Else, Environment